PELATIHAN POWER POINT INTERAKTIF DENGAN ANIMASI DI SLB NEGERI 1 KABUPATEN GOWA - Bastiana; Budiman, Andi; Zulfitrah; Pristiwaluyo, Triyanto (Transpublika Publisher, 2022)
Teachers at SLB Negeri 1 Gowa are facing problems engaging interactive learning that is relevant to the current pandemic. They must present classes that are not only online-deliverable but also engaging, interactive, and entertaining for students. To address this issue, teachers must receive training that will assist them in creating engaging and dynamic learning materials that are also simple to create. The training's intention is for teachers to be able to develop interactive powerpoints with animation on their own. Participants can use animation to produce interactive power points as a result of this study. Some participants have done amazingly well. The conclusion is that after engaging in training on how to create interactive power presentations using animation, teachers in SLB Negeri 1 Gowa Regency improved their knowledge and skills. Given the teachers' output in the form of an interactive video created and posted to their YouTube channel, it is recommended that other schools enhance their teachers' knowledge and skills in creating interactive power points through training. The training is designed to provide children with special needs with engaging and interactive learning opportunities.